PENGEMBANGAN KETERAMPILAN MENULIS KARANGAN NARASI MENGGUNAKAN METODE PENGELOMPOKKAN IDE (CLUSTERING) BERBASIS MEDIA GAMBAR FOTOGRAFI SISWA KELAS VI SD IT AL-MUNAYA PRUM DANAMON TANJUNG ANOM KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG TAHUN PELAJARAN 2 - Ajeng Munaya Aulannida; Sutikno; Rahmat Kartolo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this study is whether there is an increase in the ability to write narrative essays through the idea grouping method (clustering) based on photographic image media in grade VI students of SD IT Al-Munaya Prum Danamon Tanjung Anom Village in the 2024-2025 Academic Year? This study aims to describe the increase in the ability to write narrative essays through the idea grouping method (clustering) based on photographic image media in grade VI students of SD IT Al-Munaya Prum Danamon Tanjung Anom Village in the 2024-2025 Academic Year. The type of research used is Classroom Action Research (CAR) using 3 cycles, namely cycles I, II and III, in general there are four stages that are passed in carrying out Classroom Action Research (CAR), namely planning, implementation, observation and reflection. The subjects in this study were 42 grade VI students of SD IT Al-Munaya Prum Danamon Tanjung Anom Village in the 2024-2025 Academic Year. The learning outcomes of the pre-cycle were in the very poor criteria. After the teaching and learning process using the idea grouping method (clustering) was completed, it was found that in cycle I the percentage of classical student completion was 54.76% of 23 people. When compared with the criteria for the level of success of the action, the student completion in cycle I was in the sufficient criteria; the increase in cycle II was 14.28% because the percentage of learning outcomes was the same as 69.04%. The increase in results from cycle II to cycle III was the same as 21.43%. Thus, in cycle III, the learning outcomes were the same as 90.47%; when compared with the criteria for the level of success of the action, the learning outcomes were very good. From the results of the study, it was concluded that through the idea grouping method (clustering) based on photographic image media, it can improve the ability to write narrative essays of class V VI students of SD IT Al-Munaya Prum Danamon, Tanjung Anom Village, Academic Year 2024-2025. Thus, the hypothesis proposed can be accepted as true.